BAT99-9 – a WC4 Wolf−Rayet star with nitrogen emission: evidence for binary evolution?. Issue 2 (5th March 2021) - Hillier, D John; Aadland, Erin; Massey, Philip; Morrell, Nidia
ABSTRACT: An analysis of the Large Magellanic Cloud (LMC) WC4 star BAT99-9 (HD 32125, FD 4, Brey 7, WS 3) shows that the star still contains photospheric nitrogen. Three N emission features (N v λλ1238, 1242, N iv λ1719, and N iv λλ3479–3485) are unambiguously identified in the spectrum. cmfgen models of the star yield an N/C ratio of 0.004 ± 0.002 (by number) and a C/He ratio of $0.15_{-0.05}^{+0.10}$ . Due to the similarity of BAT99-9 to other WC4 stars, and the good fit achieved by cmfgen to both the classic WC4 spectrum and the N lines, we argue that the N lines are intrinsic to BAT99-9. An examination of a limited set of rotating models for single-star evolution at LMC and Galactic metallicities shows that a model with a Galactic metallicity ( z = 0.014) and a progenitor mass of around 50 M⊙ can have an N/C ratio similar to, or larger than, what we observe for a significant fraction of its lifetime. However, the LMC models ( z = 0.006) are inconsistent with the observations. Both the single and binary BPASS models predict that many WC stars can have an N/C ratio similar to, or larger than, what we observe for a significant fraction of their lifetime. While the binary models cover a wider range of luminosities and provide a somewhat better match to BAT99-9, it is not currently possible to rule out BAT99-9 being formed through single-star evolution, given the uncertainties in mass-loss rates, and the treatment of convection and mixing processes.